Assessing Attractiveness of Banking Industry of Bangladesh by Applying Porter’s 5 Forces Model - Mehjabeen, Lamiya (International Journal of Business and Management Future, 2018)
Banking industry is considered as one of the most significant drivers in strengthening the soundness of an economy in terms of investment, job creation, income generation, facilitating flow of funds nationally and globally. It is assumed that the present state and attractiveness of the industry can be assessed by applying Porter’s Five Forces Model. Porter’s model incorporates five dimensions i.e. Competitive Rivalry, Bargaining Power of Suppliers, Bargaining Power of Buyers, Threat of Substitutes and Threat of New Entrants. It has been objectively assessed that Competitive Rivalry is negative as 57 banks operate with more than 9000+ branches where the market share is segregated. Bargaining Power of Buyers is high as the customers are very rate sensitive while Threat of New Entrants is also negative. Mobile Financial Services (MFS) are gaining huge momentum. The Bargaining Power of Suppliers is not high as there are idle fund of Tk 1140 billion and shareholders are risk averse. Threat of Substitutes is also negative considering the similar lending and deposit services by the NBFIs and MFS substituting the transfer of funds. Considering the negative dimensions (4) over positive (1), it can be inferred that currently the industry is not attractive along with other factors that have influence on the Five Forces.